X+4=3x-6

Simple and best practice solution for X+4=3x-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X+4=3x-6 equation:


Simplifying
X + 4 = 3x + -6

Reorder the terms:
4 + X = 3x + -6

Reorder the terms:
4 + X = -6 + 3x

Solving
4 + X = -6 + 3x

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4 + X = -6 + -4 + 3x

Combine like terms: 4 + -4 = 0
0 + X = -6 + -4 + 3x
X = -6 + -4 + 3x

Combine like terms: -6 + -4 = -10
X = -10 + 3x

Simplifying
X = -10 + 3x

See similar equations:

| (12-4x)+(5-7x)=23 | | x^3+3*x+2=0 | | y=28-3(6) | | y=28-3(5) | | y=28-3(3) | | y=28-3(2) | | 20=40-4f | | 3(k+4)=12k-6 | | 6X+20=14x-68 | | x-6y=3v | | 76-7x=29x+16 | | 2x=8+2 | | 8(x+1)=2(x-2) | | 94-2x=25x+19 | | 8x-4=58 | | 7z-2=3z+6 | | 10-8x=82-29x | | 7x+5=54 | | 15-4e=3 | | 3e-3=18 | | 4x=88 | | 6x=88 | | -15-2x=13-9x | | 3y+3=18-2y | | 5-9x=45-23x | | 6x+39=16x-42 | | 5x+20=10x+10 | | 3(w-2)=12 | | 6a=17.4 | | 2a(3a-2)=0 | | 208-4x=32+20 | | t(4t-7)=0 |

Equations solver categories